2006
DOI: 10.1080/13803390590935408
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Alcohol Use/Abuse, HIV Infection and Neuropsychological Performance in African American Men

Abstract: This study examines the impact of alcohol use and HIV infection on neuropsychological performance in a sample of 497 community-resident African American men. HIV serostatus and alcohol use (during the past 12 months) exerted an interactive effect on psychomotor speed, reaction time, and motor speed, and in general, HIV infected heavy drinkers evidenced significantly poorer performance than other HIV positive subjects. Main effects for HIV serostatus were noted for reaction time, with seronegative men performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
1
30
1
3
Order By: Relevance
“…This study illustrates many of the difficulties associated with recruiting groups of participants who differ in their degree and duration of alcohol use but who are otherwise comparable in terms of demographic and other variables that might be expected to influence the performance on standardized cognitive tests. Heavy alcohol use can be associated with a number of medical comorbidities that may influence the pattern and degree of neurocognitive abnormalities, 66 and it is not surprising that the study by Durvasula et al 65 showed that the subjects with the highest level of alcohol use also were significantly more likely to have had a history of closed head injury and loss of consciousness than were the subjects with more modest or no alcohol use. There was also no adjustment for the level of premorbid IQ in this study, which is known to have significant effects on overall levels of neurocognitive performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study illustrates many of the difficulties associated with recruiting groups of participants who differ in their degree and duration of alcohol use but who are otherwise comparable in terms of demographic and other variables that might be expected to influence the performance on standardized cognitive tests. Heavy alcohol use can be associated with a number of medical comorbidities that may influence the pattern and degree of neurocognitive abnormalities, 66 and it is not surprising that the study by Durvasula et al 65 showed that the subjects with the highest level of alcohol use also were significantly more likely to have had a history of closed head injury and loss of consciousness than were the subjects with more modest or no alcohol use. There was also no adjustment for the level of premorbid IQ in this study, which is known to have significant effects on overall levels of neurocognitive performance.…”
mentioning
confidence: 99%
“…In a large community sample of 497 African-American men, Durvasula et al 65 examined the effect of alcohol and serostatus on neurocognitive performance. They found that their seropositive participants with the heaviest alcohol use had lower performance in some cognitive domains compared with seropositives who were drinking less alcohol and also compared with seronegative heavy drinkers.…”
mentioning
confidence: 99%
“…They found that alcohol and HIV exerted independent effects on cognitive performance but failed to find an interaction effect. In contrast, Durvasula et al [51], using data from the above referenced AAHP study, did demonstrate an interaction between HIV and alcohol use, with HIV+ heavy drinkers evidencing disproportionately poorer performance on measures of reaction time and motor speed relative to HIV+ subjects who did not drink to excess.…”
Section: The Independent and Interactive Effects Of Hiv And Substancementioning
confidence: 90%
“…drinks/month past 3 years) HIV-infected individuals. Similarly, no differences in verbal or non-verbal memory emerged in a comparison of HIV-infected and HIV-uninfected AfricanAmericans with no drinking and light, moderate and heavy drinking [45]. Finally, no differences in learning and memory were observed in a comparison of HIV positive and HIV negative males with and without a history of alcohol abuse [46].…”
Section: Introductionmentioning
confidence: 96%